Evolution of dislocation density distributions in copper during tensile deformation - Jiang, J; Britton, T; Wilkinson, A (2013)
The evolution of dislocation storage in deformed copper was studied with cross-correlation-based high-resolution electron backscatter diffraction. Maps of 500 μm × 500 μm areas with 0.5 μm step size were collected and analysed for samples deformed in tension to 0%, 6%, 10%, 22.5% and 40% plastic strain. These maps cover ∼1500 grains each while also containing very good resolution of the geometrically necessary dislocation (GND) content. We find that the average GND density increases with imposed macroscopic strain in accord with Ashby's theory of work hardening. The dislocation density distributions can be described well with a log-normal function. These data sets are very rich and provide ample data such that quantitative statistical analysis can also be performed to assess the impact of grain morphology and local crystallography on the storage of dislocations and resultant deformation patterning. Higher GND densities accumulate near grain boundaries and triple junctions as anticipated by Ashby's theory, while lower densities are rather more spread through the material. At lower strains (≤6%) the grain-averaged GND density was higher in smaller grains, showing a good correlation with the reciprocal of the grain size. When combined with a Taylor hardening model this last observation is consistent with the Hall-Petch grain size effect for the yield or flow stress. © 2013 Acta Materialia Inc.